SAFETY CULTURE AND RESILIENCE ENGINEERING IN HOSPITAL EMERGENCIES: A SCOPING REVIEW OF THE LITERATURE WITH A FOCUS ON OCCUPATIONAL SAFETY - Barbosa Nunes, Tamires Fernanda; Vergara, Lizandra Garcia Lupi; Vaz, Caroline Rodrigues (Revista Científica da Faculdade de Educação e Meio Ambiente, 2025)
Safety culture and resilience engineering represent fundamental concepts in ensuring safety within hospital environments. Safety culture reflects behavioral patterns that signify an organization’s commitment to its workers’ safety, health, and well-being. Resilience engineering focuses on designing systems and processes capable of adapting to, learning from, and responding to complex conditions and unexpected events. Therefore, this scoping review of the literature explored mechanisms for evaluating both processes in hospital emergency settings, specifically concerning occupational safety. Publications on the subject were searched in the PubMed, Scopus, Web of Science, and Google Scholar databases. The screening process included 36 studies, divided into mechanisms for evaluating Safety Culture (n=27) and mechanisms for assessing Resilience Engineering (n=9). The results demonstrated that the safety attitudes questionnaire was the most frequently utilized tool for assessing safety culture and the resilience assessment grid for resilience engineering. These approaches were found to contribute to assessing occupational safety, although few methods are used to operationalize and measure it. Additionally, there is inconsistency in defining the dimensions of safety culture among professionals and researchers in occupational health and safety, leading to safety culture frequently being confused with safety climate.